2016
DOI: 10.5853/jos.2016.01144
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke Mood and Emotional Disturbances: Pharmacological Therapy Based on Mechanisms

Abstract: Post-stroke mood and emotional disturbances are frequent and diverse in their manifestations. Out of the many post-stroke disturbances, post-stroke depression, post-stroke anxiety, post-stroke emotional incontinence, post-stroke anger proneness, and post-stroke fatigue are frequent and important symptoms. These symptoms are distressing for both the patients and their caregivers, and negatively influence the patient’s quality of life. Unfortunately, these emotional disturbances are not apparent and are therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 154 publications
(197 reference statements)
4
88
0
10
Order By: Relevance
“…On the contrary, we did not find an association between polymorphisms associated with serotonin metabolism and PSF. Our results are in line with the previous study that reported no effect of selective serotonin reuptake inhibitors on PSF [21,22] . Our results, however, could not completely exclude the possibility of an association between 5-HTTLPR and PSF because we did not evaluate the 5-HT receptor subtype HTR2A gene, which is known to be associated with CFS [16] .…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, we did not find an association between polymorphisms associated with serotonin metabolism and PSF. Our results are in line with the previous study that reported no effect of selective serotonin reuptake inhibitors on PSF [21,22] . Our results, however, could not completely exclude the possibility of an association between 5-HTTLPR and PSF because we did not evaluate the 5-HT receptor subtype HTR2A gene, which is known to be associated with CFS [16] .…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous studies that showed that improvement of motor dysfunction by SSRI therapy occurred regardless of poststroke depressive symptoms 10. Given that serotonin is involved in the pathogenesis of depression,37 this dissociative effect of SERT gene polymorphisms needs discussion. SSRIs are known to be involved in complex signalling cascades, which result in increased expression of neurotrophic factors, enhanced hippocampal neurogenesis, the inhibition of inflammatory cytokines and subsequent augmentation of neurogenesis, increased axonal sprouting and the development of new synapses 1–3 38 39.…”
Section: Discussionsupporting
confidence: 90%
“…Because the TPH2 gene is associated with depression in subjects without stroke (Gao et al., ) one may argue that our findings are not specific to PSD. It has been shown that PSD is associated with a complex etio‐pathogenesis that includes psychologic responses secondary to sudden functional disability, neurochemical changes due to brain damage, and difficult familial, social, or environmental situations (Kim, ). On top of these, certain genetic traits for depression may be related to the development of PSD, and our results may provide some evidence to support this argument.…”
Section: Discussionmentioning
confidence: 99%